Strategic Approaches to Digital Advertising for Consumer Engagement in the Digital Era - Setiawati, Iis (Journal of Economicate Studies, 2022)
This study analyzes strategic approaches in digital advertising to engage consumers in today’s data-driven and platform-diverse digital era. It explores how businesses develop advertising strategies by aligning content, platform choice, and ethical considerations with evolving consumer behavior. Using qualitative analysis of academic literature and institutional sources, the research identifies key elements such as content personalization, cross-platform integration, and real-time responsiveness as success factors. The findings highlight the importance of strategic coherence grounded in theoretical models like the Technology Acceptance Model and Consumer Engagement Theory. The study also examines ethical concerns, including privacy and data use, which increasingly shape consumer trust. It offers practical and theoretical insights for marketers seeking to refine their digital strategies in emerging markets. The research contributes to a deeper understanding of how advertising campaigns are designed, adjusted, and evaluated in complex digital environments.